Analysis of the implementation of the combined Suricata intrusion detection system with a machine learning model - Blinov, Maksym; Svatovskiy, Igor (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2025)
Relevance. The study presents a comparative analysis of intrusion detection and prevention systems (IDS/IPS) functioning with and without artificial intelligence (AI) integration. Conventional signature-based systems such as Suricata effectively detect known threats but often fail to recognize new or modified attack patterns. Therefore, integrating AI technologies offers a promising way to enhance adaptability and minimize false positives.Objective. The study aimed to evaluate the efficiency of the open-source Suricata system in two configurations: a standard mode using signature-based detection and a modified version enhanced with a machine learning module. The goal was to determine how AI affects detection accuracy, response time, and alert reliability under various cyberattack scenarios, including DoS and brute-force attempts. The experiment was performed in a virtualized environment consisting of three nodes: Kali Linux as the attacker, Windows 10 as the target, and Suricata as the monitoring system.Research Methods. Methods of statistical modeling and comparative analysis were applied. In its base form, Suricata relied solely on predefined rules, while in the AI-extended version, an analytical module employing the Random Forest algorithm processed log data to classify network events. The model was trained on labeled datasets containing normal and malicious traffic, using extracted statistical and protocol-level features.Results. Analysis showed that the baseline Suricata achieved a detection rate of 87–92% and precision of 80–85%, generating excessive alerts during DoS simulations. After AI integration, the number of alerts decreased more than threefold, the detection rate increased to 93–96%, and precision rose to 90–94%. Additionally, the average response time was reduced to 1–1.5 seconds.Conclusions. Integrating machine learning algorithms into the capabilities of Suricata IDS significantly increased its efficiency, reduced the number of false positives, and improved the system's ability to adapt to new cyber threats. The results confirm that combining a signature approach with AI-based analytics provides a more reliable and intelligent approach to modern network security.